Effects of piezoelectric based nonlinear energy sink on the aeroelastic behavior of a typical section - Otsubo, Gabriela Mayumi de Freitas (2020)
The attenuation of undesired structural vibrations is of interest in a variety of engineering applications ranging from industrial machines to aerospace structures. Especially for lightweight and flexible structures used in aircraft and spacecraft systems, piezoelectric shunt damping offers remarkable advantages as an electronic damping approach without the mass loading effects of conventional and bulky vibration damping methods. Linear piezoelectric vibration absorbers are tuned to a specific frequency and, therefore, their control performance may be significantly reduced if the target frequency is modified due to variation of environmental conditions, fabrication tolerances, parameter uncertainties, or nonlinearities, among others. Researchers have explored different types of nonlinear piezoelectric shunt circuits to enhance the vibration suppression bandwidth of piezoelectric absorbers and, therefore, overcome the limitations of linear piezoelectric absorbers. This work extends this topic by investigating numerically and experimentally the influence of nonlinear piezoelectric vibration absorbers on the behavior of linear and nonlinear aeroelastic systems. A typical section with two degrees of freedom is used and the electromechanical coupling is added to the plunge degree of freedom. Later, a concentrated nonlinearity, free play, is added to the typical section. For each typical section, the short-circuit configuration is assumed as reference case and the increase in the flutter speed is obtained numerically and experimentally. The results are presented in time and frequency domain and show increases of flutter speed from 2.5 % for the experimental nonlinear typical section to 3.7 % for the experimental linear one.